KEPENTINGAN PEMERINTAH INDONESIA BEKERJASAMA DENGAN TRANSPARENCY INTERNATIONAL DALAM UPAYA MEMINIMALISIR TINGKAT KORUPSI DI INDONESIA - Fauzi, Miftahul; Fachri, Yuli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
According to the Corruption Perception Index 2015 published by Transparency International that ranks countries from less corrupt (1) to most corrupt (168) , Indonesia is on 88th out of 168th countries and with the socre 36 out of 100, 36 (definitely corrupt) and 100 (clean) . It indicates that corruption is still an issue happening mostly in public sector and other areas. Even though Indonesia has spreaded no effort to combat against corruption through enforcing law enforcement conducted by the police, prosecutors and State Audit Agency (BPK) and also establishing Corruption Eradication Comission (KPK), an International Nongovernmental Organization namely Transparency International (TI) also involves participating in fighting against corruption through a join collaboration with the government since 2011-2015 to publish the Corruption Perception Index. This research aims to explain the interest of Indonesia to collaborate with TI in attempt to eradicate corruption.This research theoretically has built by using Neorealism perspective on International Relations and supported by Nation-State theor. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods.This research also using subnational group as the level of analyze, the focus on this research is explain the interest of Indonesia to collaborate with TI in attempt to combat against corruption through conducting a join research on mapping out the level or corruption in Indonesia and the result of the survey is published at Corruption Perception Index.Keywords: Corruption Perception Index, Survey, TI, Neorealism, Nation-State.